Sleep disturbances in caregivers of patients with advanced cancer: A systematic review. Issue 1 (18th January 2017) - Maltby, Kirstin F.; Sanderson, Christine R.; Lobb, Elizabeth A.; Phillips, Jane L.
ABSTRACT: Objective: Sleep disturbances are a common issue for those who provide informal care to someone with a life-limiting condition. The negative consequences of poor sleep are well documented. The purpose of the present study was to determine the sleep patterns of caregivers of patients with advanced cancer. Method: An extensive systematic review of studies reporting empirical sleep data was undertaken in 2015 in accordance with the PRISMA Statement. A total of eight electronic databases were searched, with no date restrictions imposed. Additionally, a search of the bibliographies of the studies identified during the electronic search was conducted. Search terms included: "sleep, " "insomnia, " "sleep disturbance, " "circadian rhythm, " "caregiver, " "carer, " "advanced cancer, " "palliative cancer, " and MESH suggestions. The inclusion criteria required studies to be in English and to report primary qualitative and/or quantitative research that examined sleep in caregivers of patients with advanced cancer. Unpublished studies, conference papers, and dissertations were excluded. Results: Overall, 10 studies met the inclusion criteria and were included in the review. Two major findings emerged from the data synthesis. First, at least 72% of caregivers reported moderate to severe sleep disturbance as measured by the Pittsburgh Sleep Quality Index. Second, objective measurement of caregivers' sleep identified that some caregivers experienced up to a 44% reduction in their total sleep time compared to the recommended eight hours. Significance of Results: Reduction in total sleep time appears to be the biggest issue facing caregivers' sleep. Future studies need to explore the specific factors that cause these sleep disturbances and thus help to identify interventions to optimize sleep.